Mind the Seat Limit: On Capacity Management in Public Automated Shuttles - Mirnig, Alexander G.; Gärtner, Magdalena; Wallner, Vivien; Füssl, Elisabeth; Ausserer, Karin; Rieß, Jannik; Meschtscherjakov, Alexander (Frontiers in Human Dynamics, 2021)
Public transport is increasingly being automated, with automated shuttles being an attractive alternative in areas, where traffic constraints limit the deployment of large buses (city centres) or low degrees of utilization render manual operation expensive (last mile). The lower capacities of shuttles combined with the absence of a human driver or conductor makes capacity management a potentially greater challenge for the user. In this paper, we present the results from a series of studies, which investigated capacity management in automated shuttles via currently available interaction means in public transport (auditory announcements, in-shuttle display, booking application). We found that measures during and after boarding alone are insufficient and that capacity management in automated shuttle requires a higher emphasis on the planning and pre-boarding stages, which can result in reduced flexibility when boarding automated shuttles as opposed to non-automated public buses. We conclude with a discussion and recommendations on how to design for capacity management in automated public transport shuttles.